Efficient callus formation and these callus antibacterial activities of a valuable medicinal plant Stachys cretica L. subsp. garana (Boiss) Rech - Ozdemir, Fethi Ahmet; Kocak, Gulden; Kursat, Murat (Progress in Nutrition, 2017)
An effective in vitro callus regeneration was developed for Stachys cretica L. subsp. garana (Boiss) Rech., a valuable medicinal plant. Callus formation in in vitro of S. cretica subsp. garana was induced on hypocotyl explants cultured on  2,4-D with and without TDZ (9 combinations). The findings of the results showed that callus formation percentage of the treatments ranged from 83.66±0.13 to 46.33±1.23. Maximum callus formation percentage was observed on explants cultured on MS medium having 4 mg/l 2,4-D. Minimum callus formation percentage was seen on MS medium having 2 mg/l 2,4-D + 0.2 mg/l TDZ. Callus weight of the treatments ranged from 352.32±0.63 to 163.12±1.56. Increase concentration of TDZ significantly decrease in callus weight. Antibacterial activity was evaluated inhibition of growth Staphylococcus aureus COWAN 1 and Bacillus subtilis var. niger ATCC 10 in the callus extracts determined by disc diffusion methodology. No antibacterial activities were detected in control group, acetone extracts and hexane extract of callus regenerated on MS medium having 4 mg/l NAA. Antibacterial activity for Staphylococcus aureus COWAN 1 and Bacillus subtilis var. niger ATCC 10 was noted on methanolic callus extracts. Moreover, the present study results showed that the increase of TDZ concentration in the callus regeneration environment resulted in a increase of antibacterial activity. The results of the present finding showed that extracts of calli developed through influenced therapeutic potential by the plant growth regulators treatments. The in vitro induced S. cretica subsp. garana Calli can be used as healing and curing agent in  pharmaceuticals.